Propriedades físicas, químicas, nutricionais e tecnológicas de feijões (Phaseolus vulgaris L.) de diferentes grupos de cor - Pinto, Jennifer Vieira (2016)
We aimed to characterize the physical, chemical, technological, nutritional and functional properties of beans from different color groups in order to feed the Embrapa Rice and Beans database, contributing with useful information to the scientific community and food industries. Carioca (Pérola - "PER" and BRS Estilo - "ETL"), black (BRS Esteio - "EST" and IPR Uirapuru - "IPR") and special beans (BRS Agreste - "AGR" and BRS Pitanga - "PIT") were grown in June (winter / 2014) in Santo Antônio de Goiás -GO, and analyzed for: the 100-seed weight, size, sphericity, color, moisture, water activity and density. Flours were analyzed for: granulometry, color, water absorption and solubility index, oil retention capacity, foam properties, emulsifiers, stabilizers, paste properties, kaempferol content, proximal composition, minerals, amino acid profile, protein in vitro digestibility and anti-nutritional factors. Black grains were lighter, and carioca, heavier. Grains of "PER" presented greater length and "AGR", greater sphericity; "ETL" tended to lighter grains; "PIT", "IPR" and "EST", darker. Flours of "EST" and "IPR" had greater uniformity; "ETL", "PER" and "AGR" presented lighter and more yellow flours; the "IPR" flour showed higher values of water absorption; "EST", higher values of oil absorption; the "PIT", better solubility; AGR, higher foaming (pH 2.5); the "IPR", the higher maximum viscosity. Grains of "PIT" presented higher concentration of kaempferol; "PIT" and "PER", higher protein levels; "EST" had more lipids; and "AGR", more carbohydrates. All flours had high mineral contents. Black beans showed higher levels of essential and non-essential amino acids, followed by special and carioca beans; "EST" had the lowest Essential Amino Acid Score (EAS) (1.20), and "ETL", highest EAS (1.40); "EST", lower protein digestibility; carioca and special beans, higher levels of phytic acid; "PIT" showed higher molar ratio (phytate: iron) and "AGR", higher molar ratio (phytate: zinc); "PER", lower tannin contents; "IPR", lower levels of trypsin inhibitors and "PIT", greater inhibition of α-amylase. The specialty beans presented excellent physical, chemical, technological, nutritional and functional characteristics, and can be used as ingredients of new products by the food industry.